Efficacy and safety of Qixue Tongzhi Granule in improving the exercise capacity of stable coronary artery disease: study protocol for a multicenter, randomized, double-blind, placebo-controlled trial - Chao, Tiantian; Sun, Jinghui; Huan, Na; Ge, Yaru; Wang, Chenglong (Frontiers in Cardiovascular Medicine, 2023)
Background Despite optimal medical therapy, patients with stable coronary artery disease (SCAD) still have a high risk of recurrent cardiovascular events. Exercise capacity measured by cardiopulmonary exercise testing (CPET) is a good surrogate marker for the long-term prognosis of SCAD. Qixue Tongzhi Granule (QTG) is created by academician Chen Keji and has the function of tonifying qi, promoting blood circulation, and regulating qi-flowing. This trial aims to investigate the efficacy and safety of QTG in improving exercise tolerance, alleviating angina pectoris and anxiety/depression symptoms, promoting health-related quality of life, and reducing the risk of adverse cardiovascular events in subjects with SCAD. Methods This is a randomized, double-blind, placebo-controlled trial. 150 SCAD patients with qi deficiency, blood stasis, and liver qi stagnation syndrome are enrolled. Patients will be randomly allocated to the QTG or placebo groups at a 1:1 ratio. QTG and placebo will be added to the modern guideline-directed medical therapy for 12 weeks and patients will be followed up for another 24 weeks. The primary outcome is the improvement of metabolic equivalents measured by CPET. The secondary outcomes are cumulative incidence of composite endpoint events, other indicators in CPET, changes in the Seattle Angina Questionnaire, traditional Chinese medicine syndrome scale, 12 items of Short Form Health Survey Questionnaire, Patient Health Questionnaire-9, and Generalized Anxiety Disorder-7, changes of ST-T segment in the electrocardiogram, improvement of left ventricular ejection fraction and left ventricular end-diastolic diameter in echocardiography. In addition, metabolomics analysis will be performed based on blood samples. Adverse events and safety evaluations will also be documented. A full analysis set, per protocol set, and safety analysis set will be conducted. Discussion This clinical trial can enrich treatment options for CHD patients with low cardiorespiratory fitness and psychological imbalance, and it may also create a new situation for promoting the application of traditional Chinese medicine in cardiac rehabilitation. Clinical Trial Registration: [http://www.chictr.org.cn], identifier: [ChiCTR2200058988].